The effect of information exchange on food loss in the milk supply chain in Banyumas, Indonesia - Mohammad Zidni Assifakhan Khoeri; Fauzan Romadlon; Halim Qista Karima (AGROINTEK, 2026)
Dairy farming in Indonesia is now experiencing significant development. In the milk supply chain, the increase in the use of milk as a raw material makes the milk processing industry increase its supply by 10% annually. However, milk production in Indonesia can only meet around 22% of the total. It means a gap of around 78% shall be imported. The imbalance between the demand and production causes Indonesia to lack self-sufficiency. Banyumas still have traditional methods, such as milking and filtering fresh milk. Such circumstances are prone to food loss, which needs preventive action to improve an effective and efficient supply chain by emphasizing information exchange in the milk supply chain. The study aims to determine how information exchange affects food loss in the milk supply chain in Banyumas. The study used quantitative and Chi-Square to conduct statistical analysis of 46 farmers. The result showed that demographics correlate with information exchange. Furthermore, farmers should improve their knowledge about the loss in the milk supply chain. They shall improve their understanding to adopt information technology to gain accurate and up-to-date data regarding milk production. Those activities are related to preventing food loss. Therefore, stakeholders' roles, such as farmer groups and cooperatives, are significant in facilitating the activities.